CORRELATION BETWEEN UPPER TRAPEZIUS, LEVATOR SCAPULAE AND PECTORALIS MINOR MUSCLE LENGTH IN FROZEN SHOULDER – A CROSS-SECTIONAL OBSERVATIONAL STUDY (International Journal of Physiotherapy, 2020)
Background: Frozen shoulder is defined as the painful and disabling condition with unknown etiology. It has a limited shoulder range of motion due to decreased capsular flexibility and altered muscle function. Assessment on the frozen shoulder is needed, and it is vital to know the alteration in scapular muscles in the shoulder range of motion during arm elevation. The intention of conducting this study is to reach conclusions of tightness of a muscle in the upper trapezius, pectoralis minor muscle, and frozen shoulder levator scapulae showing limited ranges.Methods: In this cross-sectional observational study, 50 subjects of age 30 and above were assessed for muscle length in the frozen shoulder and unaffected shoulder. Subjects with shoulder pain with frozen shoulder stage 2 and above are allotted into the affected shoulder, and unaffected shoulder; both groups were assessed. The following parameters were measured: ROM of the shoulder, SPADI ratings, short pectoral thickness, levator scapulae length, and upper trapezium muscle length.Results: Decreased shoulder flexion, extension, abduction, and limited rotations were the problems associated with frozen shoulder. Pearson correlation coefficient for PMI and LSI shows Positive Correlation r = 40.6% on the affected side. Pearson correlation for PMI and UTI shows Positive Correlation r = 13.4%. Pearson Correlation for LSI and UTI shows Positive Correlation r= 28.1% on the affected side.Conclusion: There was a correlation between upper trapezius, levator scapulae, and pectoralis minor muscle length. Most of the affected side shoulder showed the tightness in the pectoralis minor muscle.